2023
DOI: 10.1039/d2bm01421a
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the antibacterial mechanism of Cu-enriched sol–gel coatings employing proteomics

Abstract: Advanced antibacterial biomaterials can help reduce the severe consequences of infections. Using copper compounds is an excellent option to achieve this goal; they offer a combination of regenerative and antimicrobial...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…This establishes an inflammatory microenvironment conducive to osteogenesis and heightened infection resistance (Figure 8). 130 A study by Romero‐Gavilan et al 131 has revealed that Cu 2+ supplementation influences the adsorption of proteins associated with complement, angiogenesis, and osteogenesis on material surfaces. Such an interaction bolsters both bactericidal and osteogenic properties.…”
Section: Bone Biomaterials Modified By Inorganic Active Ionsmentioning
confidence: 99%
“…This establishes an inflammatory microenvironment conducive to osteogenesis and heightened infection resistance (Figure 8). 130 A study by Romero‐Gavilan et al 131 has revealed that Cu 2+ supplementation influences the adsorption of proteins associated with complement, angiogenesis, and osteogenesis on material surfaces. Such an interaction bolsters both bactericidal and osteogenic properties.…”
Section: Bone Biomaterials Modified By Inorganic Active Ionsmentioning
confidence: 99%